2006
DOI: 10.1128/aem.01215-06
|View full text |Cite
|
Sign up to set email alerts
|

Role ofptsP,orfT, andsssRecombinase Genes in Root Colonization byPseudomonas fluorescensQ8r1-96

Abstract: Pseudomonas fluorescens Q8r1-96 produces 2,4-diacetylphloroglucinol (2,4-DAPG), a polyketide antibiotic that suppresses a wide variety of soilborne fungal pathogens, including Gaeumannomyces graminis var. tritici, which causes take-all disease of wheat. Strain Q8r1-96 is representative of the D-genotype of 2,4-DAPG producers, which are exceptional because of their ability to aggressively colonize and maintain large populations on the roots of host plants, including wheat, pea, and sugar beet. In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Furthermore, PtsP may regulate phzM indirectly by other regulators. As far as we know, the exact regulation mechanism of PtsP has not yet been clarified completely and may involve the utilization of carbon and nitrogen, rather than a promoter-specific regulatory factor (36,53,58). In this report, we provide evidence that the conversion of PCA to PYO by PhzM activity, especially at 37°C, is activated by LasI and inhibited by PtsP, although the precise regulatory mechanism remains to be further investigated in detail.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, PtsP may regulate phzM indirectly by other regulators. As far as we know, the exact regulation mechanism of PtsP has not yet been clarified completely and may involve the utilization of carbon and nitrogen, rather than a promoter-specific regulatory factor (36,53,58). In this report, we provide evidence that the conversion of PCA to PYO by PhzM activity, especially at 37°C, is activated by LasI and inhibited by PtsP, although the precise regulatory mechanism remains to be further investigated in detail.…”
Section: Discussionmentioning
confidence: 62%
“…3), suggesting that the las system directly activates phzM by recognizing the putative lux box. In previous studies (36,58), inactivation of ptsP resulted in PYO overproduction by P. aeruginosa PAO1, leading to a significant decrease in the expression of qscR and twofold and threefold increases in the expression of lasI and rhlI, respectively, and suggested that PtsP inhibited PYO production by activating qscR and repressing the las and rhl system in P. aeruginosa. Furthermore, PtsP may regulate phzM indirectly by other regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants were assayed for growth kinetics in King's B and M9 media, swimming motility, and production of exoprotease, siderophore, and 2,4-DAPG as described earlier (41,42). Longterm rhizosphere colonization assays were performed with wheat Triticum aes- tivum L. cv.…”
Section: Methodsmentioning
confidence: 99%
“…The interrupted inserts from pCR-T3SG2⌬Pst and pCR-T3SG2⌬Sac were subcloned into pEX18Tc. All pEX18Tc-based plasmids were mobilized in Q8r1-96 from E. coli S17-1(-pir), and double crossover events were selected and verified by PCR as described earlier (42).…”
Section: Methodsmentioning
confidence: 99%
“…But many other genes are also likely to be important. For example, Mavrodi et al (45) found that three genes related to pathogenicity in some pseudomonads were important for the superior root colonization of a biocontrol strain. To be sure, much work needs to be done in this area, because there are hundreds of genes per genome that are good candidates for mutational studies based on what we already know about biocontrol.…”
Section: Experimental Paths Toward a Greater Understanding Of How Secmentioning
confidence: 99%